Ritual : A Very Short Introduction - Stephenson, Barry (Oxford Oxford University Press, 2015)
Ritual is part of what it means to be human. Like sports, music, and drama, ritual defines and enriches culture, putting those who practice it in touch with sources of value and meaning larger than themselves. Ritual is unavoidable, yet it holds a place in modern life that is decidedly ambiguous. What is ritual? What does it do? Is it useful? What are the various kinds of ritual? Is ritual tradition bound and conservative or innovative and transformational? Alongside description of a number of specific rites, this Very Short Introduction explores ritual from both theoretical and historical perspectives. Barry Stephenson focuses on the places where ritual touches everyday life: in politics and power; moments of transformation in the life cycle; as performance and embodiment. He also discusses the boundaries of ritual, and how and why certain behaviors have been studied as ritual while others have not. Stephenson shows how ritual is an important vehicle for group and identity formation; how it generates and transmits beliefs and values; how it can be used to exploit and oppress; and how it has served as a touchstone for thinking about cultural origins and historical change. Encompassing the breadth and depth of modern ritual studies, Barry Stephenson's Very Short Introduction also develops a narrative of ritual's place in social and cultural life.
Include Illustrations, References and Index.
A Very Short Introduction.
Keywords: Ritual